FINANCIAL AND ECONOMIC MECHANISM OF NATIONAL FOREST POLICY IMPLEMENTATION - Chernyakevich, Lidiya Mikhailovna; Andrianov, Yuryi Semyonovich (Journal of Applied Engineering Science, 2016)
Approaches to understanding the essence of the notion of ‘forest policy’ are systematized. The contents of the state policy is covered from the view point of forest exploitation, control, protection and reproduction in the Russian Federation on the basis of concept, principles, strategic and tactical purposes of forest management. The features of the financial and economic mechanism are revealed in the field of forest relations under the conditions of federal property on forest plots in the structure of forestry fund lands and private-entrepreneurial form of forest exploitation. A fundamental law of forest exploitation in Russia is rent of forest plots, therefore the financial and economic mechanism of national forest policy implementation should be based on coordination of interests of the state (the proprietor of forest fund), business (in forest exploitation) and the population living on forested territories or near the forests. The conceptual scheme of financial and economic mechanism in the field of forest exploitation, control, protection and reproduction is developed. Such instruments of forest policy as forest planning, price system in the forest sector of economic activity, subventions on the execution of powers transferred to subjects of the Russian Federation in the field of forest relations, subsidies for a state (municipal) establishment to perform the state task services in the sphere of natural resources reproduction and exploitation are considered. The basic trends of the state industrial and national forest policies aimed at the development of the forest sector of the economics of Russia are generalized.